‘As if it was something spoken by a friend’: Political Public Relations and Digital Vote-canvassing Networks via Facebook during the 2013 Bangkok Gubernatorial Election Campaign - Pratheepwatanawong, Mukda (2017)
Social networking sites (SNSs) are an emerging channel of political mediation in Thailand for political figures to establish and develop their relationships with Thai citizens. Through focusing on the online political public relations work by candidates (and their teams) in the 2013 Bangkok gubernatorial election campaign, this thesis contributes a Thai perspective and experience to the growing literature on the use of SNSs globally in election campaigning.